Activation of Sirtuin 2 Inhibitors Employing Photoswitchable Geometry and Aqueous Solubility. (7th May 2020) - Grathwol, Christoph W.; Wössner, Nathalie; Behnisch‐Cornwell, Steven; Schulig, Lukas; Zhang, Lin; Einsle, Oliver; Jung, Manfred; Link, Andreas
Abstract: Because isoenzymes of the experimentally and therapeutically extremely relevant sirtuin family show high similarity, addressing the unique selectivity pocket of sirtuin 2 is a promising strategy towards selective inhibitors. An unrelated approach towards selective inhibition of isoenzymes with varied tissue distribution is targeted drug delivery or spatiotemporal activation by photochemical activation. Azologization of two nicotinamide‐mimicking lead structures was undertaken to combine both approaches and yielded a set of 33 azobenzenes and azopyridines that have been evaluated for their photochemical behaviour and bioactivity. For some compounds, inhibitory activity reached the sub‐micromolar range in their thermodynamically favoured E form and could be decreased by photoisomerization to the metastable Z form. Besides, derivatization with long‐chain fatty acids yielded potent sirtuin 2 inhibitors, featuring another intriguing aspect of azo‐based photoswitches. In these compounds, switching to the Z isomer increased aqueous solubility and thereby enhanced biological activity by up to a factor of 21. The biological activity of two compounds was confirmed by hyperacetylation of sirtuin specific histone proteins in a cell‐based activity assay. Abstract : Switched into action : Besides fine‐tuning molecular geometry for enzyme inhibition, photoinduced isomerization of azopyridine‐based nicotinamide mimics results in improved aqueous solubility, enforcing the effect on target protein sirtuin 2. The resulting Sirt2 inhibitor could be used to study binding events in cellular systems with spatiotemporal control by two independent molecular and supramolecular effects.